Managing Openness : Trade and Outward-oriented Growth After the Crisis - Haddad, Mona; Shepherd, Ben (World Bank, 2012)
The global financial crisis is stimulating a broad reassessment of economic integration policies in developed and developing countries alike. The crisis was associated with a great trade collapse, the sharpest in recorded history and the deepest since Second World War (Baldwin 2009). The trade collapse affected all countries and products, although to different extents. While signs of recovery are starting to solidify, deeper questioning of the causes of the crisis and the merits of globalization has surfaced. The emergence of China and the imbalances of its trade with the United States are shaking the stability of the global system. Are these imbalances sustainable, or do they need to be adjusted to avoid another global crisis? What impact will these adjustments have on the trade of developing countries if they mean that China consumes more and the United States saves more? Openness has helped support growth in many countries, to unprecedented levels in Brazil, China, Indonesia, Malaysia, and others. Yet today many are concerned that openness is creating vulnerability, and vulnerability can hurt growth. No one believes that inward orientation is the solution or that domestic consumption alone can boost growth, even in large countries. The longer-term benefits of openness more than compensate for the short-term negative impacts of trade shocks. The question is not whether to remain open but rather what kind of safety and insurance systems, at the micro and macro levels, to put in place to better hedge against shocks from globalization. As developing countries try to find answers to these questions, they also face a drastically changed trade environment. The crisis proved that protectionism is no longer the name of the game; it remained largely under control thanks to a solid multilateral regime as well as to a new system of production sharing across countries, which does not lend itself naturally to broad-based protectionism. Moreover, the role of South-South trade is growing, giving developing countries new opportunities to export and new opportunities to import cheaper capital goods, now produced in countries like China or India, that allow them to industrialize faster. Thus, while outward-oriented growth is here to stay, it needs to be put in a different perspective and packaged with additional policies. As the world emerges from the crisis, the author expect to see the development of an 'export-led growth version 2.0' model that reflects these new dynamics.